Bibliotherapy Strategy: Experimental Study To Reduce Hospitalization Stress In Pre-School Children - Kili Astarani; Selvia David Richard (Universitas STRADA Indonesia, 2020)
The research design used the Pre Experiment Design with a one-group pre-post test design. The population, preschool-aged children who experience hospitalization stress in the Karunia Room of Kediri Baptist Hospital. The sample is 15 respondents who were selected by Quota Sampling. The research variable was Bibliotherapy. The data collection process was carried out using a questionnaire. Data analysis using Paired Samples Test. The results of the research before doing bibliotherapy, stress hospitalization of preschool children were severe as 9 respondents (60.0%), mild as many as 4 respondents (26.7%), and moderate as many as 2 respondents (13.3%). The average change in stress hospitalization before and after bibliotherapy was 7.67 with a p-value of 0.000. Bibliotherapy is effective in reducing hospitalization stress in preschool children in the Karunia Room of Kediri Baptist Hospital